An evaluation of nutrition, culinary, and production interventions using African indigenous vegetables on nutrition security among smallholder farmers in Western Kenya - Merchant, Emily V.; Odendo, Martins; Maiyo, Norah; Govindasamy, Ramu; Morin, Xenia K.; Simon, James E.; Hoffman, Daniel J. (Frontiers in Nutrition, 2023)
Introduction Nutrition security continues to worsen in sub-Saharan Africa. Current research is limited on how seasonality may influence the impact of nutrition, culinary, and production interventions on food security, diet quality, and consumption of African Indigenous Vegetables (AIV); a culturally accepted source of micro-and-macronutrients that are easily produced due to their adaptation to the local environment. The objective of this study was to evaluate the programmatic impact of AIV interventions on nutrition security among smallholder farmers. Methods In a randomized control trial, five target counties in Western Kenya were randomly assigned to one of four treatments: (1) control; (2) production intervention (PI); (3) nutrition and culinary intervention (NCI); and (4) NCI and PI (NCI/PI). After the counties were randomly assigned to a treatment, 503 smallholder farmers (18–65 years) were selected from participatory farmer groups. The PI consisted of five agricultural production modules delivered between 2016 and 2019. The NCI was delivered twice: (1) household nutrition education (2017) and (2) community culinary training (2019). The NCI/PI included communities receiving both interventions at these time periods. Baseline and endline surveys were administered to all participants once in October 2016 (harvest season) and to all available participants (n = 250) once in June to July 2019 (dry season), respectively. The impact evaluation was analyzed by Household Hunger Scale (HHS), Women’s Dietary Diversity Score (WDDS), AIV consumption frequency, and AIV market availability. Statistical tests included descriptive statistics (means and frequencies), paired t-test, McNemar’s test, Wilcoxon Signed-Rank test, ANOVA test with Tukey post hoc, and χ2 test. Open-ended questions were aggregated, and responses were selected based on relevancy and thoroughness of the response to provide context to the quantitative data. A value of p < 0.05 was used to denote statistical significance. Results There was an overall decrease in WDDS, HHS, and consumption frequency between baseline and endline attributed to seasonal differences. Despite this, post-intervention, households that received NCI/PI had a higher WDDS relative to the control: WDDS 5.1 ± 1.8 vs. 4.2 ± 1.5, p = 0.035. In addition, between baseline and endline, there was an overall increase in the percentage of respondents that reported an adequate supply of key AIVs, particularly for households that received PI. Furthermore, seasonal effects caused a reported shift in the primary location for purchasing AIVs from the village to the town market. There was no reported difference in HHS. While “diet awareness” significantly influenced diet quality among the NCI treatment group, “production” was reported to have the greatest influence on diet quality among all intervention groups. Discussion The findings revealed that coupled nutrition, culinary, and production interventions could create a protective effect against seasonal fluctuations in the availability and affordability of AIV as evidenced by a higher WDDs. Conclusion and Recommendations These findings suggest that future programming and policy should focus on promoting the availability, accessibility, acceptability, and affordability of improved agronomic practices and germplasm for both smallholder farmers with particular emphasis on AIV varieties that contain high levels of micro-and macronutrients, improved agronomic characteristics (e.g., delayed flowering, multiple harvests, higher yields, and disease resistance), and are aligned with the communities’ cultural preferences. In addition, agricultural training and extension services should incorporate nutrition and culinary interventions that emphasize the importance of farmers prioritizing harvests for their household consumption.